Evaluasi Incident dan Service Request Management pada Layanan e-Visa di Kantor Imigrasi Cirebon Menggunakan ITIL 4 - Ramdani, Dzahwa Laely Putri; Hatta, Muhammad; Suwandi, Suwandi (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
This study evaluates the service maturity of the e-Visa system at the Class I TPI Cirebon Immigration Office with reference to two ITIL 4 practices: Incident Management and Service Request Management. Operationally, the office acts as a user while technical handling is centralized at a national helpdesk. A mixed-method approach was applied, combining staff/admin questionnaires with instrument validity, reliability checks, snapshot analysis of helpdesk tickets, and brief observations. The analysis identifies key issues: the absence of a locally agreed Service Level Agreement (SLA), delays in resolving high-priority incidents, and inconsistent communication of status and estimated time to resolution. Findings indicate a gap between perceived process maturity and ticket-based operational performance, especially for high-priority cases. The study proposes actionable improvements formalizing SLAs with the central team, a fast-track for urgent cases, concise submission guidance for routine requests, and results of the web-based recommendation dashboard. These results are relevant for similar user units operating under centralized support.